2012
DOI: 10.1590/s1677-04202012000300002
|View full text |Cite
|
Sign up to set email alerts
|

NaCl salinity affects germination, growth, physiology, and biochemistry of bambara groundnut

Abstract: The effects of NaCl salinity on seed germination, growth, physiology, and biochemistry of two bambara groundnut landraces (Vigna subterranea (L.) Verdc), Kakamega (white seed coat) and Mumias (red seed coat), were investigated with the aim of establishing traits, which can provide a basis for breeding to salt tolerance in groundnuts. A study was conducted under laboratorial and greenhouse conditions. Bambara groundnut seeds and plants were subjected to five concentrations of NaCl solutions with several electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 27 publications
2
41
0
1
Order By: Relevance
“…Bambara's ground nut potential of contributing to food security has fuelled an increasing research interest (Jane et al, 2012). Karikari (2001) reported that intercropping maize with Bambara nut did not affect the number of cobs and weight of seed in maize.…”
Section: Effects Of Bambara Nut Intercrop On Growth and Yield Of Maizementioning
confidence: 99%
“…Bambara's ground nut potential of contributing to food security has fuelled an increasing research interest (Jane et al, 2012). Karikari (2001) reported that intercropping maize with Bambara nut did not affect the number of cobs and weight of seed in maize.…”
Section: Effects Of Bambara Nut Intercrop On Growth and Yield Of Maizementioning
confidence: 99%
“…Desai et al (2012), em dois genótipos de sorgo submetidos a salinidade crescente da água de irrigação, em condições de casa de vegetação encontraram redução média de 94% na altura nos dois genótipos avaliados. à medida que a área foliar é reduzida contribuindo para uma menor taxa fotossintética (Falqueto et al, 2010) e, consequentemente, menor acúmulo de matéria seca (Ambede et al, 2012), como verificado nesta pesquisa.…”
Section: Resultsunclassified
“…The microbial C was estimated by the microwave irradiation extraction method (Islam and Weil 1998) using 0.5 mol L −1 sulfuric acid as extractant and extraction efficiency coefficient of 0.21. Soil respiration was estimated by CO 2 evolution for 7 days (Alef and Nannipieri 1995). Briefly, soil samples (50 g) were sealed in a 1-L pot with 10 mL of 1 mol L −1 KOH and titrated with 0.1 mol L −1 HCl.…”
Section: Methodsmentioning
confidence: 99%